A Classroom-Based Assessment of EFL Academic Essay Writing Class: Who Gets the Benefits? - Purnamasari, Asri (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2018)
Classroom-based assessment (CBA) has been implemented globally at many levels of educational system such as in the United Kingdom, Canada, Australia, New Zealand, USA, Singapore, as well as in Africa. In Indonesia, CBA might effectively be implemented in all stages of education since this way of assessment offers improvement in the teaching and learning process. This essay explores the design and implementation of CBA, which focuses on academic EFL essay writing for teacher trainees in Indonesia. Based on my reflection on taking English as a Foreign Language (EFL) Academic Essay Writing class, I found that applying a classroom-based assessment could give two benefits. The first is for the improvement of the teaching and learning process in order to reach the study objectives. The second is to facilitate the study program for creating qualified and competent English language teachers in the area of producing competent academic essay writings.